Effect of Tibial Slope on Coronal Alignment in Total Knee Arthroplasty - Betzle, Christopher J.; Bringe, Kariline E.; Horberg, John V.; Moskal, Joseph T.; Mann, John W. (The Journal of Knee Surgery, 2021)
Malalignment of total knee arthroplasty (TKA) components affects function and survivorship. Common practice is to set coronal alignment prior to adjusting slope. With improper jig placement, adjustment of the slope may alter coronal alignment. The purpose of this study was to quantify the change in coronal alignment with increasing posterior tibial slope while comparing two methods of jig fixation. A prospective consecutive series of 100 patients underwent TKA using computer navigation. Fifty patients had the extramedullary cutting jig secured proximally with one pin and 50 patients had the jig secured proximally with two pins. Coronal alignment (CA) was recorded with each increasing degree of posterior slope (PS) from 0 to 7 degrees. Mean CA and change in CA were compared between cohorts. Utilizing one pin, osteotomies drifted into varus with an average change in CA of 0.34 degrees per degree PS. At 4 degrees PS, patients started to have >3 degrees of varus with 12.0% having >3 degrees of varus at 7 degrees PS. Utilizing two pins, osteotomies drifted into valgus with an average change of 0.04 degrees in CA per degree PS. No patients in the two-pin cohort fell outside 3 degrees varus/valgus CA. CA was significantly different at all degrees of PS between the cohorts. Changes in PS influenced CA making verification of tibial cut intraoperative critical. Use of >1 pin and computer navigation were beneficial to prevent coronal plane malalignment. This relationship may explain why computer navigation has been shown to improve alignment as well as survivorship and outcomes in some patients, especially those <65 years.
Keywords: total knee arthroplasty; computer navigation; coronal alignment